Kinetic Measurements on Single-Molecule Disulfide Bond Cleavage - Liang, Jian; Fernández, Julio M (Journal of the American Chemical Society, 2011)
We use single-molecule force clamp spectroscopy (SMFCS) to explore the reactivity of tris(2-carboxyethyl)phosphine (TCEP), 1, 4-dl-dithiothreitol (DTT) and hydrosulfide anion (HS−) on disulfide bonds within a mechanically stretched polypeptide. The single-bond level bimolecular nucleophilic substitution (SN2) events are recorded at a series of precisely controlled temperatures so that the Arrhenius kinetic parameters, that is, the height of the activation energy barrier (E a) and the attempting frequency (A) of the chemical reactions, can be determined. The values of A are typically at the order of 107 M−1 s−1, which is far lower than that predicted by the transition-state theory, in which A is given by k B T/h and around 1012 M−1 s−1 at room temperature. Furthermore, E a is derived to be 30−40 kJ/mol, which can be lowered by ∼6−8% with every 100 pN mechanical force applied. The correlation of the A and E a with the molecular structures reveals that the relative magnitude of these two parameters cannot be simply judged from the size of the molecule or the nucleophilicity of the attacking atom. The comparison of the influences on the reaction rate induced by force and temperature indicates an equivalent accelerating effect by every 50 pN or 10 K increment, giving for the first time the relationship between mechanical and thermal effects on a single-molecule SN2 chemical reaction.